Dioxygen-dependent Ketolactonases of Pseudomonas putida ATCC 17453: Enigmatic Pioneering Enzymes - Andrew Willetts (Research Perspectives of Microbiology and Biotechnology Vol. 4, 2024)
2,5-diketocamphane 1,2-monooxygenase (2,5-DKCMO) and 3,6-diketocamphane 1,6-monooxygenase (3,6-DKCMO) isolated from camphor-grown Pseudomonas putida ATCC 17453, are key enantio complementary ketolactonases that promote the initial ring cleavage of the two antipodes of this natural bicyclic terpene. Their initial characterization over sixty years ago represented a seminal discovery, being the first confirmed examples of enzyme-catalysed Baeyer-Villiger oxidations. Interestingly, over the last six decades, the perceived functional nature of these oxygen-dependent biocatalysts has transmogrified significantly. Extensive studies that commenced in the mid-1960s consistently reported that the enzymes were monomeric true flavoproteins dependent on both FMNH2 and nonheme iron as bound cofactors. The role of the metal ion, in cooperation with the flavin, was considered to be essential for the activation of molecular oxygen. However, all of those criteria have been changed absolutely by subsequent studies, resulting in the enzymes currently being acknowledged to be metal ion-independent homodimeric flavin-dependent two-component monooxygenases deploying FMNH2 not as a bound cofactor, but rather as a distinct cosubstrate. That transition is a paradigm that serves to illustrate the constantly evolving nature of scientific knowledge.